2016
DOI: 10.1007/s11419-016-0315-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of heroin and its metabolites in vitreous humor and blood in a living pig model

Abstract: Vitreous humor (VH) is an alternative matrix for drug analysis in forensic toxicology. However, little is known about the distribution of xenobiotics, such as opioids, into VH in living organisms. The aim of this study was to simultaneously measure heroin and metabolite concentrations in blood and VH after injection of heroin in a living pig model. Six pigs were under non-opioid anesthesia during the surgical operation and experiment. Ocular microdialysis was used to acquire dialysate from VH, and a venous cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…These results in vitreous when compared to femoral blood are in agreement with a previous study (R 2 = 0.26; n = 40, 61 as are the results of femoral blood to cardiac blood (R 2 = 0.76) and psoas muscle (R 2 = 0.75) 16 but do not agree with the results of two other studies that showed significant correlations between femoral blood and vitreous concentrations (R 2 = 0.87; p < 0.01, n = 69 62 ), (R 2 = 0.72; p < 0.001, n = 52 60 ), and (R 2 = 0.79; p > 0.001, n = 45 16 ). The differing sets of results obtained by the various groups and this study show that although correlations may exist for populations due to differences such as individual tolerance, individual metabolism, survival time after the administration of the drug, and also postmortem redistribution, 63,64 in the absence of a femoral blood sample in a case other samples should not be used to attempt to determine the femoral blood concentration.…”
Section: Relationships Between and Femoral Blood And The Other Varimentioning
confidence: 73%
“…These results in vitreous when compared to femoral blood are in agreement with a previous study (R 2 = 0.26; n = 40, 61 as are the results of femoral blood to cardiac blood (R 2 = 0.76) and psoas muscle (R 2 = 0.75) 16 but do not agree with the results of two other studies that showed significant correlations between femoral blood and vitreous concentrations (R 2 = 0.87; p < 0.01, n = 69 62 ), (R 2 = 0.72; p < 0.001, n = 52 60 ), and (R 2 = 0.79; p > 0.001, n = 45 16 ). The differing sets of results obtained by the various groups and this study show that although correlations may exist for populations due to differences such as individual tolerance, individual metabolism, survival time after the administration of the drug, and also postmortem redistribution, 63,64 in the absence of a femoral blood sample in a case other samples should not be used to attempt to determine the femoral blood concentration.…”
Section: Relationships Between and Femoral Blood And The Other Varimentioning
confidence: 73%
“…As previously mentioned, opioid metabolites are routinely detected from postmortem human VH samples; however, these samples are often collected from overdose victims following the administration of a fatal opioid dose [ 26 , 28 , 29 , 30 , 31 , 32 ]. While it is unclear whether sub-lethal opioid doses similarly accumulate in human VH/retina, animal studies suggest that sub-lethal doses of opioids accumulate in the mammalian VH/retina following systemic exposure [ 11 , 31 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, opioid metabolites are routinely detected from postmortem human VH samples; however, these samples are often collected from overdose victims following the administration of a fatal opioid dose [ 26 , 28 , 29 , 30 , 31 , 32 ]. While it is unclear whether sub-lethal opioid doses similarly accumulate in human VH/retina, animal studies suggest that sub-lethal doses of opioids accumulate in the mammalian VH/retina following systemic exposure [ 11 , 31 , 47 ]. While the current study differs in species, treatment, and methodology, it builds on this past work by providing an examination of morphine pharmacokinetics within mouse retina following both acute and repeated systemic morphine administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations